DETERMINAN PEMANFAATAN PELAYANAN PROGRAM KB PADA PASANGAN USIA SUBUR ( PUS ) DI KELURAHAN BABURA KECAMATAN MEDAN SUNGGAL TAHUN 2012 - pahottor sabam; Siti Khadijah Nasution; Heldy BZ (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT One of the main demography issues in Indonesia is a higher growth rate of population. Nowadays, there are any efforts to control the growth rate of the population through the control of birth rate or fertility by using contraception involuntary by the fertile spouse. This research is a survey by Explanatory research approach to study the determinant influence the implementation of family planning (KB) program.. Population in this research is all of fertile spouse while the number of sample is 94 respondents. The data analysis applied in this research is logistic regression test on confidential level 95 %. The results of research indicates that there is influence of the society value (p=0,017), resource availibility  (p=0,000), the trust to family planning (KB) service (p=0,031) to the utilization of KB program while variable that has not influence is educational level, occupation, earning, perception, and attitude of the official. It is suggested to anyone who serve the family planning (KB) provide the society with extension proactively especially to the fertile spouse to enable them understand the advantages of family planning (KB) program, the side effect of the contraception tools and to change the society paradigm to the value available in society to make them trust and use KB program